Waste Management in Smart Cities: A Survey on Public Perception and the Implications for Service Level Agreements - McCurdy, A.; Peoples, C.; Moore, A.; Zoualfaghari, M. (EAI Endorsed Transactions on Smart Cities, 2021)
INTRODUCTION: Waste management in cities has not advanced at the same rate as technology in general. Furthermore, there is little evidence that citizens are satisfied with services in smart cities.OBJECTIVES: The objective of this paper is therefore to capture citizen perspectives in relation to smart city services and, specifically, that of waste management.METHODS: An online survey was disseminated using Google Forms to twenty-five homeowners within the Tourism Ireland office in Coleraine, Northern Ireland. The objective was to gather the typical citizen perspective of smart cities, their views on the meaning of ‘smart waste management’, and any features which they would like to experience with regard to their waste collection process and/or schedule in a future smart city.RESULTS: It was found that a common perception of a smart city exists, it being one concerned with efficiency and recycling; fewer citizens are, however, familiar with the term ‘smart waste management’. Homeowners generally acknowledge that improvements to their current bin collection schedule are necessary.CONCLUSION: The paper concludes with a discussion of the ways in which citizens believe that a bin collection schedule which they are in control of would be an improvement on a council-defined one. We correlate this with extensions necessary to service provisioning processes, and Service Level Agreements (SLAs), to support future smart city services.
Keywords: smart city; waste management; citizen perspectives; survey; Service Level Agreements (SLAs